2014
DOI: 10.1111/bph.12803
|View full text |Cite
|
Sign up to set email alerts
|

Targeting multiple cannabinoid anti‐tumour pathways with a resorcinol derivative leads to inhibition of advanced stages of breast cancer

Abstract: BACKGROUND AND PURPOSEThe psychoactive cannabinoid Δ 9 -tetrahydrocannabinol (THC) and the non-psychoactive cannabinoid cannabidiol (CBD) can both reduce cancer progression, each through distinct anti-tumour pathways. Our goal was to discover a compound that could efficiently target both cannabinoid anti-tumour pathways. EXPERIMENTAL APPROACHTo measure breast cancer cell proliferation/viability and invasion, MTT and Boyden chamber assays were used. Modulation of reactive oxygen species (ROS) and apoptosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 46 publications
(84 reference statements)
3
64
0
Order By: Relevance
“…This effect of CBD relies -at least partiallyon the downregulation of ID-1 (transcription factor inhibitor of DNA binding-1)(McAllister et al, 2011;Murase et al, 2014;Soroceanu et al, 2012).…”
mentioning
confidence: 99%
“…This effect of CBD relies -at least partiallyon the downregulation of ID-1 (transcription factor inhibitor of DNA binding-1)(McAllister et al, 2011;Murase et al, 2014;Soroceanu et al, 2012).…”
mentioning
confidence: 99%
“…In a model where tumors were derived from subcutaneous implanted human lung cancer cells, full reversal of CBD-dependent antitumor activity was observed in the presence of a PPRγ antagonist (Ramer et al, 2013). Finally, it was recently demonstrated that the anti-metastatic activity of CBD in a mouse model of breast cancer was not reversed in the presence of a CB 2 receptor antagonist (Murase et al, 2014). …”
Section: Non-psychoactive Plant-derived Cannabinoids As Inhibitorsmentioning
confidence: 99%
“…The ability of CBD to enhance the activity of THC was associated with the production of ROS leading to inhibition of pERK and activation of multiple caspases. In a more recent study, it was reported in a mouse model of breast cancer metastasis that CBD was more potent than THC at inhibiting the formation of lung metastatic foci (McAllister et al, 2007; Murase et al, 2014). …”
Section: Non-psychoactive Plant-derived Cannabinoids As Inhibitorsmentioning
confidence: 99%
“…It dampens nitric oxide (NO) production in animal models of acute and chronic inflammation (24,152,162,247,267,600,654,758), the expression of inflammatory cytokines and transcription factors [interleukin (IL)-1␤, IL-2, IL-6, IL-8, tumor necrosis factor (TNF)-␣, interferon (IFN)-␥, CCL3, CCL4, NF-B] (39, 419), and reactive oxygen species (ROS) production (320, 767). However, in many types of cancer cells, CBD is capable of generating ROS, thereby inducing cytotoxicity or apoptosis and autophagy (478,540,543,547,552,610,862). CBD also improves mithochondrial function and enhances mithochondrial biogenesis in vivo under pathological conditions (327).…”
Section: Introduction: Cannabis and Cannabinoids Ancient Drugs Bementioning
confidence: 99%